2012
DOI: 10.1093/glycob/cws076
|View full text |Cite
|
Sign up to set email alerts
|

Presence of terminal N-acetylgalactosamineβ1-4N-acetylglucosamine residues on O-linked oligosaccharides from gastric MUC5AC: Involvement in Helicobacter pylori colonization?

Abstract: Isolation of MUC5AC mucins from the gastric mucosa from two secretor individuals (one from normal mucosa from a patient with gastric cancer and one from a control) showed different abilities to bind and induce the proliferation of the Helicobacter pylori strain J99. Analysis of the released O-linked oligosaccharides by LC-MS from these individuals showed a very heterogeneous mixture of species from the cancer patient containing both neutral and sialylated structures, whereas the normal sample showed dominating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…In agreement with previous studies (38,41), the core 2 O-glycans were the dominant structure in human gastric mucins. The interindividual heterogeneity of gastric O-glycans was mainly because of ABH and Lewis blood group epitopes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (38,41), the core 2 O-glycans were the dominant structure in human gastric mucins. The interindividual heterogeneity of gastric O-glycans was mainly because of ABH and Lewis blood group epitopes.…”
Section: Discussionsupporting
confidence: 93%
“…3B, an extended core 1 like glycan was found to be capped with an ␣1,4-GlcNAc-like epitope ( 0,2 A 2 -H 2 O ions at m/z 304). The presence of LacdiNAc like structures on human gastric O-glycans was first described in our previous study based on O-glycan profiles from P10H and P5TA-AS (38). In this study, samples from additional 8 individuals were included.…”
Section: Lacdinac-like and ␣14-glcnac-like Epitopes On Human Gastricmentioning
confidence: 95%
“…The gastric mucin MUC5AC with N-acetylgalactosamine-β-1,4-N-acetylglucosamine residues on O-linked oligosaccharides from gastric MUC5AC has also been reported to act as receptor for BabA[68,69]. Most recent immunohistochemistry laden tissue profiling assay using mice model showed that the expression of Leb structure is a mucin α 1,2-fucosyltransferase (FUT2) enzyme dependent and consequently identified MUC5AC as the carrier molecule of the Leb structure[70].…”
Section: Literature Searchmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) is a known receptor for bacterial LPS [44]. The LabA adhesin specifically binds to GalNAcβ1-4GlcNAc motif, also known as N,N′-diacetyllactosediamine [lacdiNAc]), carried by MUC5AC mucins [45, 46]. However, orthologues of the human cell receptors and antigens have yet to be described from the epithelium of the gastrodermis of the gut of O. viverrini .…”
Section: Opisthorchis Is a Reservoir Of H Pylori And Host-bacterimentioning
confidence: 99%